2011
DOI: 10.1136/bjsm.2011.085506
|View full text |Cite
|
Sign up to set email alerts
|

Is activation of transversus abdominis and obliquus internus abdominis associated with long-term changes in chronic low back pain? A prospective study with 1-year follow-up

Abstract: Improved transversus abdominis lateral slide among participants with low baseline slide was associated with clinically important long-term pain reduction. High baseline slide and delayed onset of abdominal muscles after the intervention period were weakly associated with higher pain at 1-year follow-up. Clinical Trial Registration number The study was preregistered in ClinicalTrials.gov with identifier NCT00201513.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 34 publications
(61 reference statements)
0
31
0
Order By: Relevance
“…11,[32][33][34] Q ualSyst scores ranged from 0.19 to 1. Most studies were found to have m oderate to high quality, 11,13,[32][33][34][35][36][37][38][39][40][41][42][43][44] with only 5 studies scoring below 0.75 31,[45][46][47][48] (Table 1 ). Results of the Q AREL ranged from three to seven (Table 2 ).…”
Section: Risk O F Bias Wit Hin St Udiesmentioning
confidence: 99%
“…11,[32][33][34] Q ualSyst scores ranged from 0.19 to 1. Most studies were found to have m oderate to high quality, 11,13,[32][33][34][35][36][37][38][39][40][41][42][43][44] with only 5 studies scoring below 0.75 31,[45][46][47][48] (Table 1 ). Results of the Q AREL ranged from three to seven (Table 2 ).…”
Section: Risk O F Bias Wit Hin St Udiesmentioning
confidence: 99%
“…The findings from the studies in this thesis identified that the deep trunk muscles were the most likely to be affected by LBP in dancers. There is substantial evidence that training programs which target the transversus abdominis and multifidus muscles in people with LBP are successful in improving muscle function (Hides et al 2009, Tsao et al 2010a, Unsgaard-Tøndel et al 2012) and increasing muscle size (Danneels et al 2001, Hides et al 2008b. There is also evidence that exercise programs which target these muscles are associated with reduction of symptoms of LBP such as pain and disability (Ferreira et al 2010, O'Sullivan et al 1997, Unsgaard-Tøndel et al 2012, Vasseljen and Fladmark 2010.…”
Section: Implications For Motor Control Of the Trunk (Studies I-iv)mentioning
confidence: 99%
“…Furthermore, the changes in muscle morphology and behaviour associated with this intervention are linked to clinically meaningful outcomes such as reduced pain and disability in people with LBP. For example, improved contraction of transversus abdominis muscles in people who have chronic LBP and low baseline measures of contraction is associated with long-term pain reduction (Unsgaard-Tøndel et al 2012) and reduced disability (Ferreira et al 2010). The efficacy of motor control training to reduce pain and disability and recurrence (Hides et al 2001) associated with LBP has also been shown in specific groups such as: people with acute LBP (Hides et al 2001), people with spondylolisthesis (O'Sullivan et al 1997), and athletes with LBP (Hides et al 2008b).…”
Section: Hagins 2011mentioning
confidence: 99%
See 2 more Smart Citations